Prognostic significance of sVEGFR-1 in identification of resistance to cisplatin and paclitaxel chemotherapy in ovarian cancer patients - Bednarek, Wiesława; Barczyński, Bartłomiej; Kotarski, Jan (Menopause Review/Przegląd Menopauzalny, 2005)
Objectives: Most of the patients (>80%) with ovarian cancer require primary debulking surgery and adjuvant chemotherapy as a standard treatment. Chemotherapy including paclitaxel and cisplatin/carboplatin is mainly used as the first-line chemotherapy. Its limited efficacy is connected with resistance to cytostatics aquired by tumor cells. Vascular endothelial growth factor (VEGF) was identified in many tumors, including ovarian cancer. High prgnostic value of this proangiogenic factor was presented. Increased expression of VEGFR in tumor tissue is correlated with poor prognosis for the patients. Design: The aim of the study was to evaluate prognostic significance of soluble VEGF receptor form (sVEGFR-1) in identification of resistance to cisplatin and paclitaxel first-line chemotherapy in ovarian cancer patients. Materials and methods: The study was performed in a group of 52 women aged 30-77 (median 52 years) treated in 1st Department of Gynecology, Medical University of Lublin, Poland. All patients underwent debulking surgery and adjuvant chemotherapy. The concentration of sVEGFR-1 was assessed preoperatively in blood serum with the use of ELISA method. Resistance to chemotherapy was evaluated according to WHO criteria and Christian and Trimble cisplatin resistance principles (1994). Results: There were 14 cases of chemotherapy resistant disease. Median concentration of sVEGFR-1 was 0.01 ng/ml, range 0-0.374 ng/ml, and was statistically correlated with incidence of resistance to cytostatics. The risk of chemotherapy resistance is significantly higher in patients with elevated sVEGFR-1 serum levels. Conclusions: sVEGFR-1 serum concentration evaluation may become helpful in identification of resistance to cisplatin and paclitaxel chemotherapy in ovarian cancer patients and may present patients who need modification of adjuvant treatment.